2016
DOI: 10.2217/pgs-2015-0008
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Pharmacogenomics of β-Lactam-Induced Neutropenia

Abstract: Aim: Determine if individuals with β-lactam induced neutropenia have polymorphisms that impair function of MRP4 or OAT1/OAT3. Methods: Subjects with β-lactam induced neutropenia were compared to controls for the presence of MRP4 and OAT1/OAT3 polymorphisms, estimated plasma trough concentrations and area under the curve. Results: Subjects with a homozygous polymorphism at MRP4 3348 A to G were 5.3 times more likely to develop neutropenia (p = 0.171). No statistical differences were noted in pharmacokinetic par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Although no clear evidence has been provided, the dose‐related inhibitory effect of beta‐lactam antibiotics on granulopoiesis has been postulated to compromise the ability of the bone marrow to compensate for the immune destruction of neutrophils . Finally, a possible pharmacogenetic polymorphism involving MRP4 3348 A to G or myeloperoxidase has been suggested .…”
Section: Discussionmentioning
confidence: 99%
“…Although no clear evidence has been provided, the dose‐related inhibitory effect of beta‐lactam antibiotics on granulopoiesis has been postulated to compromise the ability of the bone marrow to compensate for the immune destruction of neutrophils . Finally, a possible pharmacogenetic polymorphism involving MRP4 3348 A to G or myeloperoxidase has been suggested .…”
Section: Discussionmentioning
confidence: 99%
“…3,4,8,[10][11][12][13][14][15][16][17][18][19]68,69 Genetic variation causing predisposition to drug-induced neutropenia has been described and may play a role by increasing risk of a reaction to a specific agent. 70,71 A recent review of drug-induced agranulocytosis concluded that the available evidence supports an immunemediated mechanism as the primary pathogenesis. 71 Specific findings from case series involving β-lactams include drug-dependent antineutrophil antibodies and leukocyte agglutination, possibly induced by accumulation of reactive metabolites over several days of therapy.…”
Section: Pathogenesismentioning
confidence: 99%
“…Mice lacking MRP4 and OAT3 have demonstrated increased renal and plasma concentrations of β‐lactam antibiotics, and a separate case‐control study found patients with polymorphisms to MRP4 were found to have a higher odds of developing neutropenia than those without the polymorphism . These data suggest MRP4 and OAT1/OAT3 transporters may play a role in protection against bone marrow toxicity …”
Section: Discussionmentioning
confidence: 97%
“…Other β‐lactam toxicities, such as neurotoxicity, seem to support a dose‐dependent relationship . Polymorphisms in efflux transporter multidrug resistance protein 4 (MRP4) and uptake transporters organic anion transporters 1 and 3 (OAT1/OAT3), both substrates for β‐lactam antibiotics, may also play a role in β‐lactam–associated neutropenia . Mice lacking MRP4 and OAT3 have demonstrated increased renal and plasma concentrations of β‐lactam antibiotics, and a separate case‐control study found patients with polymorphisms to MRP4 were found to have a higher odds of developing neutropenia than those without the polymorphism .…”
Section: Discussionmentioning
confidence: 99%